Humour and the Performance of Power in South Asia
1 online resource (248 pages).
Keywords: This book critically examines the role and politics of humour and the performance of power in South Asia. What does humour do and how does it manifest when lived political circumstances experience ruptures or instability? Can humour that emerges in such circumstances be viewed as a specific narrative on the nature of democracy in the region? Drawing upon essays from India, Sri Lanka and Bangladesh, this volume discusses many crucial historical and contemporary themes, including dance-drama performances in northern India; caste and stand-up comedy in India; cartoon narratives of citizens⁰́₉ anxieties; civic participation through social media memes in Sri Lanka; media, politics and humorous public in Bangladesh; the politics of performance in India; and the influence of humour and satire as political commentaries. The volume explores the impact of humour in South Asian folklore, ritual performances, media and journalism, and online technologies. This topical and interdisciplinary book will be essential for scholars and researchers of cultural studies, political science, sociology and social anthropology, media and communication studies, theatre and performance studies, and South Asian studies.